Control of unmanned aerial vehicles - Plaksina O. M. (Scientific studies and modern education, 2019)
familiarity with the management of unmanned aerial vehicles, the study of UAV behavior depending on the flight mode
Keywords: квадрокоптер; беспилотные летательные аппараты; unmanned aerial vehicles; БПЛА; drone; дрон; UAVs; quadrocopter